Correction: Coming of age in recovery: The prevalence and correlates of substance use recovery status among adolescents and emerging adults. - Douglas C Smith; Crystal A Reinhart; Shahana Begum; Janaka Kosgolla; John F Kelly; Brandon G Bergman; Marni Basic (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295330.].